The Influence of Communication Ethics on the Accuracy of Indonesian in Digital Writing of Generation Alpha - Hutagalung, Heriyawan; Situmorang, Mulkan Andika; Devi Kristina H (Jurnal Multidisiplin Sahombu, 2025)
This study aims to analyze the influence of communication ethics on the accuracy of Indonesian language use in digital writing by Generation Alpha. The phenomenon of increasing writing activity on social media and digital platforms by elementary and secondary school students indicates a decline in language accuracy, both in terms of spelling, sentence structure, and word choice. Through a quantitative approach with a survey method, 120 respondents from grades 5–8 were collected to fill out a questionnaire that measured aspects of digital communication ethics (politeness, responsibility, empathy, and ethical awareness) and their Indonesian language accuracy. The results of a linear regression analysis showed that communication ethics had a significant influence on language accuracy (R² = 0.48, p < 0.05). Politeness and responsibility were the dominant predictors that correlated positively with appropriate language use. These findings indicate the importance of integrating digital ethics and Indonesian language learning to foster good language awareness in cyberspace. This study recommends strengthening ethical digital literacy as part of the elementary and secondary education curriculum.